Coimobilização de amilases em matriz porosa de gelatina e alginato de cálcio reticulados - Frota, Elionio Galvão (2018)
Amylases are enzymes in the industry accounting for 25 to 30% of the world's enzyme market, being used in the food, beverage, pharmaceutical and biofuel industries. Most of the enzymes used are still used in their free form and stabilized in solutions, however, the use of immobilized enzymes may have benefits such as recovery and greater stability of the biocatalyst. The study of low cost natural supports, such as gelatine, has been carried out in order to make the process cheaper. Immobilization studies focused primarily on the immobilization of a single enzyme. However, in many cases a single enzyme can not completely catalyze the desired reactions and several enzymes are needed in sequence, as in the case of saccharification of the starch. The association of two or more enzymes in immobilized systems has been studied for industrial use in order to improve catalytic efficiency. However, few studies report the joint immobilization or coimobilization of glycoamylase and α-amylase. Thus, the aim of this study was to evaluate whether the immobilization of the α-amylase and glycoamylase enzymes could bring benefits to the starch hydrolysis processes. α-amylase (Liquozyme ® Supra 2.2X) and glycoamylase (AMG ® 300L) enzymes were coimobilized into two distinct supports (gelatin and gelatin/calcium alginate) cross-linked with glutaraldehyde or Ca2+respectively. The impact of glutaraldehyde on the catalytic activity of the immobilized enzymes was evaluated. Optimum pH and temperature studies, immobilization yield, reuse and saccharification of starch were performed. The substrates were characterized for their chemical composition by FTIR, thermal behavior by DSC and TGA, morphology, porosity, degree of crosslinking, compressive strength, solubility and swelling. The results obtained showed that the two enzymes used showed similar behavior regarding the optimum pH and temperature parameters, which suggests the possibility of promoting their joint immobilization in the same matrix. After coimobilization, in both substrates, the enzymes were stable in higher temperatures. Glutaraldehyde cross-linked gelatin support gave the enzymes stability at more acidic pH. The increase in glutaraldehyde concentration negatively affected the enzymatic activities. However, at low concentrations the immobilization efficiency was satisfactory. The immobilized could be reused in up to 8 consecutive hydrolysis cycles and were more efficient in the saccharification of the starch than the free enzymes under the same conditions. Supports composition showed the interaction between gelatin and alginate in the composite support. Crosslinking could be detected by changing the interactions in the polymer molecular structure. Crosslinking did not affect the thermal behavior, but had an impact on the mechanical strength, solubility and swelling of the supports. In addition, both supports presented porous morphology, but the effective porosity was low probably due to the strong interactions between their constituents. From the results it is possible to infer that the coimobilization of amylases is a useful procedure since it can allow improvements in the catalytic efficiency in enzymatic chain reactions. Crosslinked support with glutaraldehyde may also be established as the most suitable for use in coimobilization. However, the immobilization in crosslinked support with Ca 2+also presented promising characteristics regarding catalytic activity, although its greater structural instability is a critical point.